STATE BUDGET OF KAZAKHSTAN: PROBLEMS OF FINANCING AND USE - Sabirova, R.K.; Adietova, E.M.; Bisembieva, Zh.K. (Academic Journal of Physical and Chemical Sciences, 2018)
The state budget for the purpose of reorienting the economy to large financial investments requires the search for sources of structural changes, the determination of the ratio between state funds in the form of budgetary appropriations and the own funds of enterprises. Despite the annual increase in state budget expenditures, their effectiveness is decreasing. In the authors' opinion, the budget classification of the Republic of Kazakhstan is used to compile and implement budgets and ensure comparability of budget indicators at all levels of the budget system of the Republic of Kazakhstan. Budget classification is a grouping of incomes and expenditures of budgets of all levels of the budgetary system and sources of financing of deficits of these budgets with assignment to classification objects of grouping codes